2019
DOI: 10.1111/ipd.12476
|View full text |Cite
|
Sign up to set email alerts
|

Validation of different Cariogram settings and factor combinations in preschool children from areas with high caries risk

Abstract: Background Caries risk assessment in preschool children has been limited validated. Aim To validate caries predictive ability of Cariogram using different combinations of factors and settings in preschool children from areas with high caries risk. Design Two to five years old children (N = 175) were examined for caries (cavitated and non‐cavitated lesions), at baseline and after 1 and 2 years. Mutans streptococci counts (MS) and saliva buffer capacity (SBC) were measured with chair side tests. Diet and oral he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…The Cariogram, an interactive computer-based caries risk assessment programme, has developed rapidly in the past years, with many related studies and high evaluations. It has been used to evaluate the caries risk of various populations, including normal populations of different ages [12,42], patients undergoing oral treatment [43,44] and patients with systemic diseases [45]. Andreas et al compared the validity of three caries risk assessment tools and concluded that Cariogram displayed a higher validity in predicting caries increment [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cariogram, an interactive computer-based caries risk assessment programme, has developed rapidly in the past years, with many related studies and high evaluations. It has been used to evaluate the caries risk of various populations, including normal populations of different ages [12,42], patients undergoing oral treatment [43,44] and patients with systemic diseases [45]. Andreas et al compared the validity of three caries risk assessment tools and concluded that Cariogram displayed a higher validity in predicting caries increment [46].…”
Section: Discussionmentioning
confidence: 99%
“…Caries risk refers to the possibility of individuals to develop carious lesions over a certain period of time [12]. Assessing caries risk is an essential element in the planning of preventive and therapeutic strategies [13].…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of caries risk based on these risk factors is considered a cornerstone of clinical decision making and disease prevention in individual patients [14] and using comprehensive and standardized tools is recommended [15]. While many have attempted to evaluate the risk of dental caries in early childhood [16][17][18], none have developed a prediction model that uses large-scale, representative survey data from the Korea National Health and Nutrition Examination Survey (KNHANES).…”
Section: Introductionmentioning
confidence: 99%
“…In this work the Cariogram used without salivary tests as a tool to interpret and map out a global risk of caries proved an accurate model, convenient to be used in clinical, low cost, teaching to the patient's motivation and easy interpretation, becoming thus an important ally in caries risk assessment, providing a more reliable diagnosis and treatment proposal, as corroborated by other authors. 7,8 The 10,11,12,13 When the ICDAS index was used to assess past / present experience, considering the initial stages of the lesion as an already established disease, an average of 11.9 was obtained in the general sample. This value is increased, as shown above, in relation to the CPOD/ceo-d of the same region, as well as also presented by SB Brasil 2010 in the State of Rio de Janeiro, a fact that can be explained due to this index providing early recognition of the disease while the DMFT / ceo-d index considers an installed disease only a cavity lesion already cavitated.…”
Section: Discussionmentioning
confidence: 99%